GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU PENDIDIKAN PANCASILA DAN KEWARGANEGAAAN (PPKN) PADA SMA NEGERI SE KABUPATEN BARITO KUALA - Henni Yusda Rahmiyanti (Jurnal Terapung : Ilmu - Ilmu Sosial, 2020)
This study uses a quantitative approach, which is a scientific method to fulfill scientific principles, namely concrete empirical, objective, measurable, rational and systematic. This study of the situational leadership style of high school principals in Barito Kuala Regency is an ex-post factor research. Because it reveals data or events that have taken place. Then trace back the existing data on the respondent without giving treatment to the variables that have been studied to determine the causes of the events under study. This type of research was chosen because in this study it aims to reveal how much influence the independent variables (situational leadership style, telling, selling, participating, and delegating) have on the dependent variable (professional competence and performance of Pancasila and Citizenship Education teachers) which is measured through a questionnaire as the main instrument. Furthermore, the data obtained is tabulated based on the scores obtained from each variable in the form of numbers and analyzed using statistics to test the hypotheses that have been formulated.